1999
DOI: 10.1080/10584589908210180
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic stress dependence of Pt hillock formation and its related electrical properties of SBT capacitor

Abstract: 1999) Intrinsic stress dependence of Pt hillock formation and its related electrical properties of SBT capacitor, The P f l i electrode stacks were deposited on the SiOxiSi substrate by DC magnetron sputtering. The Pt layers were deposited at various temperature of RT-500"C. These electrode stacks were annealed at 6 5 0 T for 30min in O2 ambient. A lot of high hillocks were observed on the Pt surface deposited at low temperatures (RT-300°C) after the anneal process. But the hillocks were decreased in both numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 4 publications
1
20
0
1
Order By: Relevance
“…Pt hillocks are a major * To whom all correspondence should be addressed. E-mail: cww2000@kaist.ac.kr concern because they can lead to capacitor shorts, as reported previously [4,5]. It has been reported that hillock formation depends strongly on the compressive stress generated during both sample preparation and post-annealing [6,7] and that the main mass transport mechanism for the growth of the hillock on the thin film with a columnar structure is the grain boundary diffusion [8,9].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Pt hillocks are a major * To whom all correspondence should be addressed. E-mail: cww2000@kaist.ac.kr concern because they can lead to capacitor shorts, as reported previously [4,5]. It has been reported that hillock formation depends strongly on the compressive stress generated during both sample preparation and post-annealing [6,7] and that the main mass transport mechanism for the growth of the hillock on the thin film with a columnar structure is the grain boundary diffusion [8,9].…”
Section: Introductionmentioning
confidence: 77%
“…It has been reported that hillock formation depends strongly on the compressive stress generated during both sample preparation and post-annealing [6,7] and that the main mass transport mechanism for the growth of the hillock on the thin film with a columnar structure is the grain boundary diffusion [8,9]. Three factors are considered in the total compressive stress of the Pt/Ti electrode stack: intrinsic stress, thermal stress, and extrinsic stress [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Hillocks began to appear on the surface at 700°C, continuing the growth process as the temperature was increased to 800°C. Researchers have reported that hillock formation plays a role the internal stress of the Pt layer during annealing [7][8][9][10]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pt hillocks are a major concern because they can lead to capacitor failure [6]. In addition, there is also a possibility that inter-diffusion between each layer creates a Pt-Ti compound, which can alter the crystal structure of the bottom electrode, affecting the orientation and crystal structure of the ferroelectric materials [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that Pt thin film deposited at room temperature has a high compressive stress and thus the hillock amount is high. In contrast, the Pt film deposited at 500°C shows strong tensile stress and thus the hillock formation is disappeared[7].…”
mentioning
confidence: 96%